Tahwiil Ar-Riwayah Al-Fata An-Nabiil ila Al-Fiilm: Dirasah Ikranisasiah li Pamusuk Eneste - Muntahana, Nuratul; Munjiah, Ma’rifatul (Buletin Al-Turas, 2024)
PurposeThe study aimed to reveal the forms of changes that occur in the plot, setting, and social values in the novel Al-Fata An-Nabiil and its film version seen from Pamusuk Aneste’s ecranization theory.MethodThis qualitative study made uses of descriptive qualitative research design. The primary data source was the novel Al-Fata An-Nabiil by Frances Hodgson Burnett and its film version by Kozo Kusuba. The data collection procedures included several techniques, including reading the novel, watching the film, and note-taking technique. In analyzing the data, researchers followed Miles and Huberman model, which comprised three steps: data reduction, data presentation, and drawing conclusions.Results/findingsThe study showed several forms of changes that occurred in plot, setting, and social values in the process of transforming the novel into the film Al-Fata An-Nabiil based on the study of by Pamusuk Aneste’s ecranization theory covering narrowing, increasing, and changing the work’s plot, its setting and its social values.ConclusionThe changing of the novel into its film version covered internal and external elements to adjust to the needs of new types of works.